2018
DOI: 10.1016/j.jarmac.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Testing encourages transfer between factual and application questions in an online learning environment.

Abstract: Quizzing improves retention compared to additional study opportunities, a phenomenon known as test-enhanced learning. Two experiments investigated whether the type of question at quiz improves retention for factual and applied course material on exams in an online college course. Students were given quizzes with either factual questions or questions designed to encourage application of a particular concept. As expected, quizzing with feedback improved exam performance compared to material that had not been qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Much of the research concerning the testing effect has used post-test questions that are either identical or very similar to the questions used during the study phase. However, some studies have demonstrated the benefit of testing for rephrased questions (McDaniel, Anderson, Derbish, & Morrisette, 2007), for analogical problem solving (Peterson & Wissman, 2018), and for inferential and application questions (Butler, 2010;Thomas, et al, 2018).…”
Section: Testing Effectmentioning
confidence: 99%
“…Much of the research concerning the testing effect has used post-test questions that are either identical or very similar to the questions used during the study phase. However, some studies have demonstrated the benefit of testing for rephrased questions (McDaniel, Anderson, Derbish, & Morrisette, 2007), for analogical problem solving (Peterson & Wissman, 2018), and for inferential and application questions (Butler, 2010;Thomas, et al, 2018).…”
Section: Testing Effectmentioning
confidence: 99%
“…Many studies on the testing effect have focused on the retrieval of facts acquired in the learning phase rather than on transfer effects (for an overview, see Carpenter, ). However, Thomas, Weywadt, Anderson, Martinez‐Papponi, and McDaniel () reported beneficial and even crossover effects of testing for different knowledge formats in an online learning environment with adult students learning about neuropsychology. Factual questions in the initial testing phase enhanced the final test performance with regard to application knowledge, whereas initial testing with application questions improved the final test performance with regard to factual knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…During that time, students likely took advantage of repeated and spaced feedback learning opportunities, plus studied relevant course materials. Postretrieval study of materials has been associated with successful transfer of different types than in the present work (e.g., McDaniel, Bugg, Liu, & Brick, ; see also Thomas, Weywadt, Anderson, Martinez‐Papponi, & McDaniel, ). Accordingly, it appears that in the absence of the added design features of McDaniel, Anderson, et al, fill‐in‐the‐blank questions with whole concept feedback will not yield transfer of learning to stimulus–response rearranged items.…”
Section: Discussionmentioning
confidence: 83%